IMPLEMENTATION OF JEMPOL MODEL IN BRANDING COCONUT SUGAR IN NGORAN VILLAGE, BLITAR REGENCY - Anita Reta Kusumawijayanti; Sutowo Sutowo; Dwi Lailatus Saadah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Ngoran Village in Nglegok District, Blitar Regency, has long been recognized as a center of coconut sugar production since the pre-independence era. However, artisans continue to market their products traditionally in bulk without strong brand identity, which reduces competitiveness in the modern market. This highlights the urgency of structured branding strategies. This study aims to design the JEMPOL Model (Jelajah Pasar, Eksplorasi Identitas, Merk, Promosi, Olah Pelanggan, dan Loyalitas) as a branding strategy for coconut sugar products. This research employed a qualitative case study approach involving 20 coconut sugar artisans selected through purposive sampling. Data were collected through direct observation and in-depth interviews, then analyzed using thematic analysis to identify key challenges and opportunities in branding development. The findings revealed that artisans face limitations in market access, product identity management, and promotional practices. These results align with previous studies that emphasize the importance of branding and marketing communication in empowering local small-scale industries to compete more effectively, thereby confirming the relevance of brand equity theory in this context. The JEMPOL Model offers a structured branding strategy that can strengthen product image, expand market networks, and improve the competitiveness of coconut sugar artisans in Ngoran Village.